1986
DOI: 10.1152/ajpregu.1986.251.2.r264
|View full text |Cite
|
Sign up to set email alerts
|

Food intake, feeding rhythm, and body mass regulation in Svalbard rock ptarmigan

Abstract: Food intake (FI), feeding activity (FA), and body mass (BM) were recorded continuously throughout a 13-mo period in Svalbard rock ptarmigan kept under natural conditions of light and ambient temperature at Svalbard (79 degrees N). FI was persistently high from March until August, including the period when daylight is continuous, whereas it was low from November until January, when it is permanently dark. From August until November, BM doubled, while FI dropped to one-third. BM fell rapidly from mid-November un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 0 publications
8
55
0
1
Order By: Relevance
“…However, during the continuous polar night, as well as during the continuous polar day, their feeding activity was intermittently continuous around the clock (Fig. 6) (Stokkan et al, 1986). In summer (the only time that was investigated), the activity pattern of the Adélie penguins in Antarctica has since been shown to be similar to that of the Svalbard ptarmigan (Wilson et al, 1989).…”
Section: Variations In Photoperiodmentioning
confidence: 91%
See 3 more Smart Citations
“…However, during the continuous polar night, as well as during the continuous polar day, their feeding activity was intermittently continuous around the clock (Fig. 6) (Stokkan et al, 1986). In summer (the only time that was investigated), the activity pattern of the Adélie penguins in Antarctica has since been shown to be similar to that of the Svalbard ptarmigan (Wilson et al, 1989).…”
Section: Variations In Photoperiodmentioning
confidence: 91%
“…However, all the fat has disappeared by February, when daylight reappears on the islands (Mortensen et al, 1983). Moreover, these changes also happen when captive birds are fed ad libitum throughout the year (Stokkan et al, 1986). The fat reserves are therefore not, as previously thought, used to supplement the daily energy budget during winter, but are instead carefully kept in store for episodes of acute starvation during winter storms (Mortensen and Blix, 1985).…”
Section: Fat Storagementioning
confidence: 98%
See 2 more Smart Citations
“…In particular, the acquisition of fat reserves in winter means that these birds experience a seasonal doubling of M b , from approximately 500g between March and August to approximately 900g in mid-November. At this time, fat content comprises as much as 32% of M b (Grammeltvedt and Steen, 1978;Mortensen et al, 1983;Stokkan et al, 1986). It has previously been found that Svalbard ptarmigan have adaptations for locomotor efficiency in both summer (Nudds et al, 2011) and winter (Lees et al, 2010), and when young (Lees et al, 2012b); however, it is unknown how the cost of incline locomotion is affected by the dramatic seasonal changes in M b .…”
Section: Introductionmentioning
confidence: 98%